√(14+x) (14*x) =56+4x
Answers
Step-by-step explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
48*x*(x+14)-((4*x+56)^2)=0
Step by step solution :
STEP
1
:
Equation at the end of step 1
48x • (x + 14) - (4x + 56)2 = 0
STEP
2
:
2.1 Evaluate : (4x+56)2 = 16x2+448x+3136
STEP
3
:
Pulling out like terms
3.1 Pull out like factors :
32x2 + 224x - 3136 = 32 • (x2 + 7x - 98)
Trying to factor by splitting the middle term
3.2 Factoring x2 + 7x - 98
The first term is, x2 its coefficient is 1 .
The middle term is, +7x its coefficient is 7 .
The last term, "the constant", is -98
Step-1 : Multiply the coefficient of the first term by the constant 1 • -98 = -98
Step-2 : Find two factors of -98 whose sum equals the coefficient of the middle term, which is 7 .
-98 + 1 = -97
-49 + 2 = -47
-14 + 7 = -7
-7 + 14 = 7 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -7 and 14
x2 - 7x + 14x - 98
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x-7)
Add up the last 2 terms, pulling out common factors :
14 • (x-7)
Step-5 : Add up the four terms of step 4 :
(x+14) • (x-7)